Improving Experiment Control in the Sonix+ Software Package - Kirilov, A. S.; Truntova, L. A. (Physics of particles and nuclei letters, 2023)
This study is aimed at improving the Sonix+ software package on the measuring setups of the IBR‑2 reactor to minimize the measurement time losses when mathematical operations (summation of matrices, construction of spectral intensity distributions on the basis of data from a list of events, etc.) are incorporated immediately into the procedure of experiment in Python (script). For this purpose, the execution of all similar operations was separated from the main script into one or several background scripts. To provide the execution of background scripts, a special class of devices was added to the package structure. In addition, the mechanism of checkpoints applied earlier to connect the user interface with the script was replaced by a new one based on Python decorators and context managers. This significantly simplified the script, increased its reliability, and reduced the time of its development or modification. The new package version was tested in October 2021 on the NERA spectrometer. In the nearest future, it is planned to prepare similar versions for all the other instruments. This study was carried out at the Frank Laboratory of Neutron Physics of the Joint Institute for Nuclear Research.